Purinergic stimulation of K+-dependent Na+/Ca2+ exchanger isoform 4 requires dual activation by PKC and CaMKII - Xu Yang (Bioscience Reports, 2013)
K+-dependent Na+/Ca2+-exchanger isoform 4 (NCXK4) is one of the most broadly expressed members of the NCKX (K+-dependent Na+/Ca2+-exchanger) family. Recent data indicate that NCKX4 plays a critical role in controlling normal Ca2+ signal dynamics in olfactory and other neurons. Synaptic Ca2+ dynamics are modulated by purinergic regulation, mediated by ATP released from synaptic vesicles or from neighbouring glial cells. Previous studies have focused on modulation of Ca2+ entry pathways that initiate signalling. Here we have investigated purinergic regulation of NCKX4, a powerful extrusion pathway that assists in terminating Ca2+ signals. NCKX4 activity was stimulated by ATP through activation of the P2Y receptor signalling pathway. Stimulation required dual activation of PKC (protein kinase C) and CaMKII (Ca2+/calmodulin-dependent protein kinase II). Mutating T312, a putative PKC phosphorylation site on NCKX4, partially prevented purinergic stimulation. These data illustrate how purinergic regulation can shape the dynamics of Ca2+ signalling by activating a signal damping and termination pathway.